Exploring the generative AI potential in the fashion design process: an experimental experience on the collaboration between fashion design practitioners and generative AI tools - Greta Rizzi; Paola Bertola (European Journal of Cultural Management and Policy)
Over recent years, the rise of Generative Artificial Intelligence (Gen AI) has led to the emergence of numerous tools for the creation of visual and textual content. This technological advancement, supported by increasingly robust data management systems and targeted research efforts in this direction, has driven the continuous refinement of Machine Learning and Deep Learning models. As a result, Gen AI tools have demonstrated ever-increasing performance, leading to their rapid adoption in various sectors, including the Cultural and Creative Industries (CCI). Here, they are being integrated into value-creation pipelines, potentially impacting both production processes and career prospects for creative professionals. As a consequence, critical questions have emerged about the widespread use of Gen AI, related to the nature of their generative capabilities, often encapsulated under the umbrella term of “computational creativity,” which has begun to challenge the traditional conception of creativity as an intrinsic and exclusive capacity of human beings, with implications across all fields in which human creativity is central, such as the design disciplines. In light of the current scenario, the presented research aims to discuss the application of Gen AI tools for image, text, and video generation in fashion design. The analysis draws on the results of a didactic laboratory entitled Artificial A(i)rchive, which involved design practitioners from the Master’s degree course in Design for the Fashion System at Politecnico di Milano. Within this workshop, the adoption of Gen AI was investigated, examining how AI was integrated at various stages of the design process and highlighting both the potential and shortcomings of applying Gen AI to support the activities of fashion designers. The article thus aims to contribute to the discussion and identification of collaborative models between fashion designers and AI, while situating the findings within a broader reflection on emerging creative practices and their potential implications.